CD4 T Follicular Helper Cells and HIV Infection: Friends or Enemies? - Moukambi, Félicien; Rodrigues, Vasco; Fortier, Yasmina; Rabezanahary, Henintsoa; Borde, Chloé; Krust, Bernard; Andreani, Guadalupe; Silvestre, Ricardo; Petrovas, Constantinos; Laforge, Mireille; Estaquier, Jérôme (Frontiers in Immunology, 2017)
Follicular T helper cells (Tfh), a subset of CD4 T lymphocytes, are essential for memory B cell activation, survival and differentiation and assist B cells in the production of antigen-specific antibodies. Work performed in recent years pointed out the importance of Tfh cells in the context of HIV and SIV infections. The importance of tissue distribution of Tfh is also an important point since their frequency differ between peripheral blood and lymph nodes compared to the spleen, the primary organ for B cell activation and differentiation. Our recent observations indicated an early and profound loss of splenic Tfh cells. The role of transcriptional activator and repressor factors that control Tfh differentiation is also discussed in the context of HIV/SIV infection. Given their importance for B cell differentiation and antibody production, accelerating the Tfh responses early during HIV/SIV infection could be promise as novel immunotherapeutic approach or alternative vaccine strategies. However, because Tfh cells are infected during the HIV/SIV infection and represent a reservoir, this may interfere with HIV vaccine strategy. Thus, Tfh represents the good and bad guy’s during HIV infection.